The eating disorder assessment for DSM‐5 (EDA‐5): Development and validation of a structured interview for feeding and eating disorders. Issue 5 (30th January 2015) - Sysko, Robyn; Glasofer, Deborah R.; Hildebrandt, Tom; Klimek, Patrycja; Mitchell, James E.; Berg, Kelly C.; Peterson, Carol B.; Wonderlich, Stephen A.; Walsh, B. Timothy
ABSTRACT Objective Existing measures for DSM‐IV eating disorder diagnoses have notable limitations, and there are important differences between DSM‐IV and DSM‐5 feeding and eating disorders. This study developed and validated a new semistructured interview, the Eating Disorders Assessment for DSM‐5 (EDA‐5). Method Two studies evaluated the utility of the EDA‐5. Study 1 compared the diagnostic validity of the EDA‐5 with the Eating Disorder Examination (EDE) and evaluated the test–retest reliability of the new measure. Study 2 compared the diagnostic validity of an EDA‐5 electronic application ("App") with clinician interview and self‐reported assessments. Results In Study 1, the kappa for EDE and EDA‐5 eating disorder diagnoses was 0.74 across all diagnoses (n = 64), with a range of κ = 0.65 for other specified feeding or eating disorder/unspecified feeding or eating disorder to κ = 0.90 for binge eating disorder. The EDA‐5 test–retest kappa coefficient was 0.87 across diagnoses. For Study 2, clinical interview versus App conditions revealed a kappa of 0.83 for all eating disorder diagnoses (n = 71). Across individual diagnostic categories, kappas ranged from 0.56 for other specified feeding or eating disorder/unspecified feeding or eating disorder to 0.94 for BN. Discussion High rates of agreement were found between diagnoses by EDA‐5 and the EDE, and EDA‐5 and clinical interviews. Because this study supports the validity of the EDA‐5 to generate DSM‐5 eating disorders and the reliability of these diagnoses, the EDA‐5 may be an option for the assessment of anorexia nervosa, bulimia nervosa, and binge eating disorder. Additional research is needed to evaluate the utility of the EDA‐5 in assessing DSM‐5 feeding disorders. © 2015 Wiley Periodicals, Inc. (Int J Eat Disord 2015; 48:452–463)